Thomas Aquinas on the passion of hope - Xu, Ke (HTS teologiese studies, 2024)
Thomas Aquinas has argued that the passion of hope is the movement of the sensitive appetite and the first of the irascible passion. The first part of the article aims to explore the cause and the mechanism of the passion of hope, and tries to clarify the relationship between the passion of hope and the perception. In human beings, it is possible that the passion of hope is caused by false judgement of the perception, which will lead to the result of false hope. In Aquinas’s argument, the problem of false hope could be solved through the moral virtue and the prudence. In the second part of this article, the aim is to analyse how the virtue of magnanimity, humility and the prudence work impact on the passion of hope and perfect it.Contribution: This research concentrates on the topic of the passion of hope of Thomas Aquinas, and provides a new perspective on the understanding of the relationship between the passion and the virtue.